1992
DOI: 10.1128/aem.58.2.703-705.1992
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of acetate utilization among strains of an aceticlastic methanogen, Methanothrix soehngenii

Abstract: The kinetics of acetate utilization by concentrated suspensions of cells was examined in five strains of Methanothrix soehngenii. The rate of acetate utilization by all strains was dependent on the initial acetate concentration and followed simple Michaelis-Menten kinetics. The ability to utilize acetate differed among the various strains of M. soehngenii and was highest in the strain designated MTAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…This threshold acetate concentration is based on values measured in this study; however, there are a wide range of kinetic values for the specific species and strains of methanogens. Ohtsubo et al (1992) studied the acetate utilization kinetics of five strains of Methanosaeta soehngenii and found a six-fold difference in k values and a three-fold difference in K S values. Thus, to some extent, the threshold acetate concentration at which Methanosarcina becomes the dominant aceticlast will depend on the species of Methanosaeta and Methanosarcina present in the digester.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This threshold acetate concentration is based on values measured in this study; however, there are a wide range of kinetic values for the specific species and strains of methanogens. Ohtsubo et al (1992) studied the acetate utilization kinetics of five strains of Methanosaeta soehngenii and found a six-fold difference in k values and a three-fold difference in K S values. Thus, to some extent, the threshold acetate concentration at which Methanosarcina becomes the dominant aceticlast will depend on the species of Methanosaeta and Methanosarcina present in the digester.…”
Section: Discussionmentioning
confidence: 99%
“…The microbial populations of each reactor were visualized through fluorescent in situ hybridization (FISH) using the Methanosarcina-genera-specific probe S-G-Msar-0821-a-A-24 (Raskin et al, 1994) (59 CGC CAT GCC TGA CAC CTA GCG AGC 39) and the Methanosaeta-family-specific probe S-F-Msae-0825-a-A-23 (Raskin et al, 1994) (59 TCG CAC CGT GGC CGA CAC CTA GC 39). The Methanosarcina-specific probe was labeled with Cy3, and the Methanosaeta specific probe was Fukuzaki et al, 1990;Huser et al, 1982;Ohtsubo et al, 1992;Patel, 1984;Zehnder et al, 1980. b Fukuzaki et al, 1990Huser et al, 1982;Ohtsubo et al, 1992;Zehnder et al, 1980.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell lysis also leads to the release of organic carbon (glucose) and nitrogen (ammonium, an additional resource in our model), which become again available for catabolism and assimilation (Azam, 1998). Physiological parameters were chosen randomly for each OTU and each phage within realistic ranges (Supporting Information Table S2), to account for the variation typically seen between strains or species (Ohtsubo et al, 1992;Mladenovska and Ahring, 2000). As we describe below, our model successfully reproduces previous experimental observations and yields novel insight into the effects of phage predation and functional redundancy on microbial community composition and function.…”
Section: Introductionmentioning
confidence: 99%
“…The half-saturation constant for H 2 uptake by a methanogenic, mixed-culture was measured using an experimental protocol which avoided mass transfer limitations and the Monod equation was modified by including the observed H2 threshold effect (Giraldo-Gomez et al, 1992), Interaggregate pH measurements using microelectrodes revealed higher interior pH values than those in the bulk liquid, The pH profiles strongly influenced the acetate utilization kinetics (affecting both K.and max)' Effectiveness factors for acetate utilization ranged from 0.57 to 0.62 and were entirely dependent on the interaggregate pH profiles (de Beer et al, 1992). The rate of acetate utilization by different strains of Methanothrix soehngenii was dependent on the bacterial strain and the initial acetate concentration and followed Michaelis-Menten kinetics (Ohtsubo et al, 1992).…”
Section: Kinetics Modeling and Simulationmentioning
confidence: 94%